Practices on Prevention and Control of Diarrheal Diseases among Adult Population in A Selected Rural Area of Bangladesh - Doha, Maheen; Haque, Syeda Rumana; Sharmin, Tohura; Tasnim, Afsara (The Journal of Ad-din Women's Medical College, 2025)
Background: Diarrhea is a waterborne disease that can be transmitted through biological and chemical contamination. Bangladesh has conditions favorable for the rapid transmission of enteric pathogens through the fecal-oral route. Infection may be transmitted during bathing, washing, drinking, in the preparation of food, or the consumption of contaminated food. Objective: To assess the knowledge and practices regarding prevention and control of diarrheal diseases among the adult population in a selected rural area of Bangladesh. Materials and Methods: It was a cross-sectional descriptive study conducted among 428 adult respondents. Data was collected by semi-structured questionnaire by face-to-face interview. This study was conducted between July and October 2023. Results: In this study highest number of the respondents 170 (39.7%) were within the age group of 2135 years. The mean (±SD) age of the respondents was 37.77 (± 20.78) years. The highest number of the respondents had secondary level education 144 (33.6%). The mean (±SD) monthly family income of the respondents was 23,327.58 (±27,10708.86) TK. Most of the respondents heard about hand hygiene 415 (97.0%). Regarding sources of drinking water, 257 (60%) used deep tube well water,138 (32.2%) drank direct supply water and 185 (43.2%) drank filter water. A few respondents 27 (6.3%) did not take ORS during diarrhea. Conclusion: Almost all the respondents heard and knew about diarrheal diseases. The majority of the respondents’ knowledge and practice about diarrheal diseases was satisfactory. As per the present study necessary measures should be taken against those who have not used ORS during diarrhea and improve their basic sanitation and personal hygiene. The Journal of Ad-din Women's Medical College; Vol. 13 (1), Jan 2025; p 9-13